Effects of larval trematode parasitism on the reproductive capacity of Manila clam Ruditapes philippinarum in a sandy-mud tidal flat on the west coast of Korea - Cho, Young-Ghan; Lee, Hye-Mi; Kim, Jeong-Hwa; Shin, Jong-Seop; Jeung, Hee-Do; Choi, Kwang-Sik (Frontiers in Marine Science, 2022)
Gonad intrusion of the larval trematodes often results in substantial damage to the reproductive capacity of some economically important marine bivalves. Such detrimental impacts of the larval trematode infection are observed in Manila clam Ruditapes philippinarum in the coastal Yellow Sea, although the effects on the host’s reproduction are poorly understood. Accordingly, this study attempts to understand the impacts of parasitism on clam reproduction using histology. Of the 1,255 adult clams collected in early June from a tidal flat on the west coast of Korea, 68 individuals (5.4%) were infected by three different larval trematodes, including Cercaria tapidis, Cercaria pectinata, and Parvatrema duboisi. Histology revealed that the uninfected clams were in the late developing or ripe stage, exhibiting fully developed gametes in the expended follicles. In contrast, clams infected by the larval trematode showed retarded gonad maturation. Some of those clams remained sexually indifferent (13/68 infected clams) or early developing (9/68 infected clams). We categorized the infection level into uninfected (0), light (1), moderate (2), heavy (3), and very heavy (4), according to the area of sporocysts occupying the histology section. The image analysis indicated that approximately 50% of the infected clams were in “heavy” and “very heavy” conditions, and they occupied 16.7% and 26.9% of the total cross-section area, respectively. The nonparametric Kruskal–Wallis’s test and the post-hoc Tukey’s test indicated that the condition index (CI) of clams in heavy and very heavy infection were significantly lower than uninfected clams. In conclusion, the larval trematodes infected about 5.4% of the clam population in the tidal flat on the west coast of Korea, and we estimated that 32.4% of the infected clams might fail to reproduce during a spawning period due to the severe infection.